Public Service Announcements on TV : An Effective Tool for Reaching Entrepreneurs in Tajikistan - Dall'Olio, Andrea (World Bank, Washington, DC, 2012)
Improving the regulatory environment - i.e., producing business-friendly regulations is often seen as the main goal of business enabling environment programs. However, an effective regulatory framework is not enough by itself: entrepreneurs and public officials have to be aware of the new regulations in order to apply them to their day-to-day business activity and ensure impact. The Tajikistan Business Enabling Environment Project took a unique approach to increasing public awareness by creating a series of public service announcements (PSAs) for television. In July 2006 the Government of Tajikistan, with help from the International Finance Corporation (IFC) Tajikistan Business Enabling Environment Project, adopted the country's first ever law regulating inspections of businesses. By doing so the government demonstrated to the public at large and the business community in particular that it was committed to putting in place business-friendly regulations. The law clearly identified the bodies entitled to carry out inspections and laid out inspection procedures aimed at bringing transparency into the inspections process and reducing corruption. At the same time, the law introduced the concept of risk-based inspections.